METACOGNITIVE–DISCURSIVE ACTIVITIES IN JUNIOR HIGH SCHOOL MATHEMATICS LEARNING: A COMPARATIVE STUDY IN SOUTHWEST SUMBA, INDONESIA - Sesilia Irmaya Bulu; Marcellinus Andy Rudhito (Sanata Dharma University Yogyakarta, 2026)
This study compares metacognitive–discursive activities in Grade-7 mathematics learning in two private Catholic junior high schools in Southwest Sumba, Indonesia: SMPK St. Paulus Karuni (n=14) and SMPK St. Aloysius Weetebula (n=13). A convergent parallel mixed-methods design was used, combining pre–post test results with classroom discourse analysis. Students completed an initial test consisting of 12 mathematics items and 6 logic items, and the same test was administered again after one semester. Classroom lessons were video-recorded and transcribed; focal segments were analyzed using a metacognitive–discursive activity category system (Karuni: 08:20–15:35; Weetebula: 44:10–51:23). Baseline results indicated similar initial achievement (combined averages 21% at Karuni and 19% at Weetebula), with both cohorts struggling on fraction items, particularly those involving unlike denominators. Discourse coding showed that Karuni displayed a more sustained metacognitive–discursive teaching culture, including more frequent student participation in explaining, justifying, and checking solutions, alongside active peer discussion and limited impact of negative discursive events. In Weetebula, metacognitive moves appeared more teacher-mediated and negative discursive events (e.g., low audibility, fragmented explanations, interruptions) occurred more frequently, reducing clarity of meaning-making. Post-test results aligned with these patterns. Karuni improved to 27% (mathematics) and 66% (logic), yielding a combined average of 34%, whereas Weetebula reached 16% (mathematics) and 36% (logic), with a combined average of 20%. Overall, the findings suggest that sustained student engagement in metacognitive–discursive interaction is associated with stronger learning development over one semester.